A learning journey to the Kingdom of Tonga: Accelerating transformative change in nutrition-sensitive value chains in Pacific islands: Promoting nutritious food systems in the Pacific islands - Sio-Ki-Sia Fonua, Finau (Technical Centre for Agricultural and Rural Cooperation, 2019)
Pacific Island countries suffer from alarming rates of non-communicable diseases (NCDs) and are consistently ranked as the most obese and diabetic in the world. At the centre of this NCD crisis is the underlying problem of consumption of processed imported foods; high in fat, salt and sugar, displacing nutritious local produce; crops and fish from the daily meals of Pacific people. In order to help address this problem, the Technical Centre for Agricultural and Rural Cooperation ACP-EU (CTA), in collaboration with MORDI Tonga Trust, the International Fund for Agricultural Development (IFAD) and the Pacific Islands Private Sector Organisation (PIPSO), organised three activities in the Kingdom of Tonga from 3 - 6 December 2018. The integrated four-day event was held under the theme Transforming Nutrition-Sensitive Value Chain Development in the Pacific Islands within the framework of the CTA/IFAD/PIPSO Innov4AgPacific project. The overall objective of which is to “Strengthen the capacity of Pacific Island countries to develop strategies and programmes that would increase accessibility of poor rural peoples to nutritious and healthy foods”.